Surface integrity-dependent nanoparticle coating efficiency: exploring sonochemically synthesized Zingiber officinale extract-based ZnO nanoparticles on Ti6Al4V - Ullen, Nuray Bekoz; Sevk, Gizem Karabulut; Ozarslan, Ali Can; Kucak, Mine (SPRINGER, 2025)
Techniques are being developed to modify and functionalize metallic biomaterials by altering their surface morphology and structure without compromising their mechanical integrity. A unique combination of properties can be imparted with surface machining and biocompatible nanocoatings, which are the main themes of this study. For this purpose, surface machining and biocompatible nanocoatings were developed to modify the morphology and structure of metallic biomaterials. Ti6Al4V alloy surfaces with three different levels of roughness were coated with ZnO nanoparticles (NPs) synthesized via a plant-mediated, ultrasound-assisted green synthesis method using ginger extract (GE) and polyethylene glycol (PEG) as a biopolymer stabilizing agent. The morphology of the synthesized organic-inorganic matrix-based ZnO NPs was characterized. Contact angles of uncoated and coated surfaces were measured to assess the effects of roughness and coatings on wettability. A detailed investigation was conducted to understand the surface characteristics of coated Ti6Al4V substrates. In vitro cell viability assays evaluated the biological response to the coatings. Results showed that spherical ZnO NPs were successfully synthesized. Increased feed rate during machining raised substrate roughness, but nanocoating reduced final roughness. Higher roughness affected the coating morphology, and contact angles increased with both roughness and coating. Contact angles were ranged from 59 degrees to 63 degrees for uncoated surfaces and 60 degrees to 67 degrees for coated samples. All samples showed cell viability above 70%, indicating no cytotoxicity. Overall, optimizing surface roughness and applying ZnO NPs coatings enabled the creation of multifunctional surfaces on Ti6Al4V alloy, making them promising for biomedical applications.
Keywords: ZINC-OXIDE; DENTAL IMPLANTS; LEAF EXTRACT; THIN-FILMS; TITANIUM; ROUGHNESS; BIOCOMPATIBILITY; TOPOGRAPHY; ADHESION; ANTIBACTERIAL; Materials Science